Effectiveness of Adding Tomato Juice to Fe Tablet Supplementation on the Hemoglobin Levels of Anemic Adolescent Girls in Class XII at SMK Negeri 1 Sukanagara, Indonesia - Sri Utami Nur Amalia; Yulianti, Lia (Journal of Anesthesiology and Clinical Research, 2024)
Introduction: Iron deficiency anemia (IDA) in adolescent girls is a serious public health problem. Iron supplementation is one of the most effective efforts to control ADB. The addition of tomato juice to Fe tablet supplementation is expected to increase iron absorption and reduce side effects. This study aims to determine the effectiveness of adding tomato juice to Fe tablet supplementation on the hemoglobin levels of anemic teenage girls in class XII at SMK Negeri 1 Sukanagara, Indonesia. Methods: This research used a quasi-experimental design with a pretest-posttest with control group design. The research sample was 60 anemic teenage girls in class Fe tablet supplementation. The intervention was carried out for 4 weeks. Hemoglobin levels were measured before and after intervention. Data were analyzed using the t-test. Results: The results showed that there was a significant difference in hemoglobin levels between the intervention group and the control group after the intervention (p<0.05). Hemoglobin levels in the intervention group increased by an average of 1.2 g/dL, while in the control group, they only increased by an average of 0.5 g/dL. Conclusion: The addition of tomato juice to Fe tablet supplementation is effective in increasing hemoglobin levels in anemic adolescent girls.